Antagonism of glucocorticoid receptor transcriptional activation by the c-Jun N-terminal kinase - Rogatsky, Inez (The National Academy of Sciences, 1998)
The mitogen-activated protein kinases ERK (extracellular signal-regulated kinase), JNK (c-Jun N-terminal kinase), and p38 phosphorylate and activate transcription factors that promote proliferative and inflammatory responses, whereas glucocorticoid receptor (GR) activation inhibits cell growth and inflammation. We demonstrate that JNK and ERK but not p38 phosphorylate GR in vitro primarily at Ser-246. Selective activation of either ERK or JNK in vivo inhibits GR-mediated transcriptional activation, which depends on receptor phosphorylation at Ser-246 by JNK but not ERK. Thus, JNK inhibits GR transcriptional activation by direct receptor phosphorylation, whereas ERK does so indirectly. We propose that phosphorylation of GR by JNK or of a GR cofactor by ERK provides mechanisms to ensure the rapid inhibition of GR-dependent gene expression when it conflicts with mitogenic or proinflammatory signals.